How to Fulfill Carotenoid Needs during Pregnancy and for the Growth and Development of Infants and Children – A Review. Issue 3 (9th July 2021) - Prihastyanti, Monika Nur Utami; Chandra, Rosita Dwi; Lukitasari, Diah Mustika
Abstract : Society's latest lifestyle has developed to a more rapid mobilization and advanced technology which makes people's daily needs of nutrients have altered as well. This phenomenon comes to consequences where healthy diet has been neglected and people consume food only to fulfill the calories—which can be supplied by consumption of macronutrients such as carbohydrates, proteins, and fats. To reach good health status, intake of micronutrients is also important to maintain biological process occurred inside human's body as the deficiency of them may interfere the continuity of metabolic regulation of the body. Carotenoids have been known as pigments that are synthesized only in plants. The roles of carotenoids for the improvement of health have been investigated by numerous research reports, and they are highlighted in this review paper, especially their role for pregnancy and also, growth and development of infants and children. Readers will be able to read recommendation of carotenoid sources and their carotenoid composition that can be consumed periodically. Furthermore, several techniques on processing technology were also elaborated to improve people's knowledge to preserve carotenoids in the ingredients. GRAPHICAL ABSTRACT: